Social conflict management framework for project viability: Case studies from Korean megaprojects. Issue 8 (November 2017) - Lee, Changjun; Won, Jin Woo; Jang, Woosik; Jung, Wooyong; Han, Seung Heon; Kwak, Young Hoon
Abstract: Traditionally, conflict management in construction projects has focused on disagreement among internal stakeholders, such as employer, contractors, and subcontractors. However, as social consciousness and personal welfare demands increase, social conflicts among external stakeholders, such as local residents, local and central governments, and NGOs, have become more critical factors in enhancing project viability. In Korea, these conflicts have an impact of US 70 billion annually on social costs. To alleviate social conflicts and costs, this study aims to propose a conflict management framework based on twenty-two representative public construction projects. This study identifies and frames the various causes, impacts, and resolutions of conflicts through the case history of project viability. Through these findings, five types of conflict scenarios were derived: project termination, early mitigation, late mitigation, project enforcement, and late occurrence. Furthermore, this study suggests root causes, pathway of conflict propagation, and characteristics of each conflict scenario, which will assist project stakeholders in developing sustainable management for conflict solutions in line with each project's unique situation. Highlights: Social conflicts of public construction projects are analyzed. Five types of social conflict scenarios are derived. Root causes and pathway characteristics of each conflict scenario are suggested. Sustainable management for conflict solutions are discussed.